Zur Stellung des Matorischen innerhalb der samojedischen Sprachen - Helimski, Eugen (University of Szeged, 2022)
This is an unpublished text from the legacy of Eugen Helimski, which discusses the position of Mator inside the Samoyed branch. It shows that Mator may have had specific relations with the North Samoyedic languages, especially with Nenets and Enets, and its ties with Kamas are of thee late, areal origin.